Hawker Food Development in Pattaya Municipality - ปั้นสุวรรณ อภิเศก; สุนิตย์สกุล สุธีร์ (Journal of the Faculty of Arts, Silpakorn University, 2020)
Hawking is an informal economic activity found in many cities, including Pataya. As a result of a survey, on socio-economics and attitudes towards food hawkers from 300 consumers in Pattaya, it was found that hawker food was an important source for the local people, particularly on those low and middle incomes. Most of consumers were satisfied with the hawker food locations and price, while cleanliness and location were most important factors when making choice. In the future, both areas – the cleanliness and location - should be improved the food sanitation requirements.